Técnicas do cálculo numérico aplicadas no ensino médio - Pereira, Paulenrike Gonçalves (2015)
In face of the need to determine values , satisfying equations of the form f(x) = 0, the purpose is this paper to present three important methods isolating roots, considered in mathematical literature as elementary. First of all, this work puts out some definitions and exposes the reader to the impossibility of creating formulas, for roots of polynomial equations greater than tree degrees. However, it shows techniques that provide acceptable approximation in minimizing the error possible, how close to zero can the result can be reached. In order to optimize speidof these techmiques, this paper also discusses some techniques to isolate roots to identying intervals that may contain them. Futhermore, this paper raises a comparison between the three methods of calculating the zeros of functions, addressing possible advantages and disadvantages of them. Finally, it presents the experience of teaching one of these contents in high school, assessing their compatibility to the students intellectual level of the students and showing some results of that.